Facial Transformation in a Class III Surgical Case - Smruti Bhusan Nanda (Institute of Medico-legal Publications Pvt Ltd, 2020)
Orthodontic problems that cannot be treated by growth modification/camouflage treatment needs to becorrected by surgical method. The envelope of discrepancy needs to be respected while handling these cases.This case report presents an adult female patient with Skeletal Class II malocclusion.